Chloroplastic metabolic engineering coupled with isoprenoid pool enhancement for committed taxanes biosynthesis in Nicotiana benthamiana - Jianhua Li (Nature Portfolio, 2019)
Engineering Taxol pathway in microbes needs to overcome the difficulty of expressing plant P450 enzymes. Here, the authors use a compartmentalized metabolic engineering strategy to construct the taxanes production pathway in chloroplasts of Nicotiana benthamiana and realize the production of taxadience-5α-ol.